2008
DOI: 10.1111/j.1438-8677.2008.00162.x
|View full text |Cite
|
Sign up to set email alerts
|

MYB72, a node of convergence in induced systemic resistance triggered by a fungal and a bacterial beneficial microbe

Abstract: Colonisation of plant roots by selected beneficial Trichoderma fungi or Pseudomonas bacteria can result in the activation of a systemic defence response that is effective against a broad spectrum of pathogens. In Arabidopsis thaliana, induced systemic resistance (ISR) triggered by the rhizobacterial strain Pseudomonas fluorescens WCS417r is regulated by a jasmonic acid‐ and ethylene‐dependent defence signalling pathway. Jasmonic acid and ethylene also play a role in Trichoderma‐induced resistance. To further i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
196
3
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 251 publications
(215 citation statements)
references
References 44 publications
(54 reference statements)
9
196
3
4
Order By: Relevance
“…The functions of MYB proteins have been investigated in numerous plant species such as Arabidopsis, maize, cotton, rice (Oryza sativa), petunia (Petunia hybrida), snapdragon (Antirrhinum majus), grapevine (Vitis vinifera L.), poplar (Populus tremuloides) and apple (Malus domestica), using both genetic and molecular analyses. In the past decade, the R2R3-MYB genes have been extensively studied and members of the MYB family have been found to be involved in a variety of biological functions like phenylpropanoid metabolism (Grotewold et al 1994;Hichri et al 2011), biotic and abiotic stress (Segarra et al 2009;Lippold et al 2009), cell shape such as Am MIXTA (Noda et al 1994), differentiation (Oppenheimer et al 1991;Kang et al 2009;Xie et al 2010), hormone responses i.e. AtMYB2 (Urao et al 1993), GAMYB and CpMYB (Gubler et al 1995 ;Iturriaga et al 1996), formation of B-type cyclin (Ito et al 2001) or during plant defense reactions i.e.…”
Section: Functions Of Mybmentioning
confidence: 99%
See 1 more Smart Citation
“…The functions of MYB proteins have been investigated in numerous plant species such as Arabidopsis, maize, cotton, rice (Oryza sativa), petunia (Petunia hybrida), snapdragon (Antirrhinum majus), grapevine (Vitis vinifera L.), poplar (Populus tremuloides) and apple (Malus domestica), using both genetic and molecular analyses. In the past decade, the R2R3-MYB genes have been extensively studied and members of the MYB family have been found to be involved in a variety of biological functions like phenylpropanoid metabolism (Grotewold et al 1994;Hichri et al 2011), biotic and abiotic stress (Segarra et al 2009;Lippold et al 2009), cell shape such as Am MIXTA (Noda et al 1994), differentiation (Oppenheimer et al 1991;Kang et al 2009;Xie et al 2010), hormone responses i.e. AtMYB2 (Urao et al 1993), GAMYB and CpMYB (Gubler et al 1995 ;Iturriaga et al 1996), formation of B-type cyclin (Ito et al 2001) or during plant defense reactions i.e.…”
Section: Functions Of Mybmentioning
confidence: 99%
“…Raffaele et al (2008) proposed that AtMYB30 modulated hypersensitive response via very-long-chain fatty acids (VLCFAs) by themselves or VLCFA derivatives and thus playing a role in programmed cell death. Segarra et al (2009) and Van der Ent et al (2008) demonstrated that the defence pathways triggered by beneficial Trichoderma, Rhizobacteria and Pseudomonas spp. strains were highly similar and root-specific transcription factor MYB72 functioned as an early node of convergence in the signalling pathways that were induced by these different beneficial microorganisms playing role in defence response in Arabidopsis.…”
Section: Biotic Stressmentioning
confidence: 99%
“…have been achieved to prevent crop losses due to diseases (Cook 2000), it is estimated that plant diseases cause a 20% yield loss in food and cash crops worldwide (Schumann and D'Arcy 2006). Disease incidence can be minimized by agricultural practices such as crop rotation, the application of chemical pesticides and breeding of resistant crop varieties.…”
mentioning
confidence: 99%
“…There are multiple mechanisms by which naturally occurring beneficial bacteria and fungi can suppress disease incidence or severity, including antibiosis, competition for nutrients and space, and the production of lyctic enzymes (Weller 1988;Chet et al 1990;Chet and Inbar 1994;Handelsman and Stabb 1996;Raaijmakers et al 2002;Haas and Defago 2005;Van Loon 2007). Of special interest is the enhancement of plant innate defense responses against pathogens by beneficial bacteria and fungi that occur naturally on plant roots (Zehnder et al 2001;Kloepper et al 2004;Hoitink et al 2006;Van Wees et al 2008;Segarra et al 2009). This induced resistance of plant defenses is effective against a wide variety of plant pathogens for prolonged periods.…”
mentioning
confidence: 99%
“…For instance, Trichoderma species is plant growth promoting fungus that is commercially available and widely used in agriculture that induces systemic resistance against microbial pathogens in plants (Harman et al, 2004;Trillas et al, 2009;Segarra et al, 2009). When the Trichoderma spp.…”
Section: The Use Of Microbial Cellmentioning
confidence: 99%